Immune biology of allogeneic hematopoietic stem cell transplantation models in discovery and translation - Blazar, Bruce R.; Sociâe, Gâerard (Amsterdam Boston Elsevier/AP, 2013)
This book provides clinical and scientific researchers with a deep understanding of the current research and the implications for translational practice. By providing an overview of immune biology of HSCT, an explanation of immune rejection and detail on antigens and their role in HSCT success, this book embraces biologists and clinicians who need a broad view of the deeply complex processes involved. It then moves on to discuss the immunobiology mechanisms that influence graft-versus-host disease (GVHD), graft-versus-leukemia (GVL) effect, and transplantation success. Using illustrative figures, highlighting key issues, describing recent successes and discussing unanswered questions, this book sums up the current state of HSCT to enhance the prospects for the future.
The clinical significance of non-classical HLA genes: HLA-E, (HLA-F), HLA-G and MIC genesConclusions; Acknowledgments; References; Chapter 3 -- The impact of minor histocompatibility antigens in allogeneic stem cell transplantation; From immunobiology to the impact of mHags in GVHD and GVT; Murine mHags, challenges for the human system; Immunobiology and biochemical identity of mHags; Mechanisms of generation of mHags; The impact of individual mHags on GVHD and GVT; To match or to mismatch: paradigm shifts in the mHag field; Hematopoietic mHags: ideal targets for separating GVT from GVHD.
Includes bibliographical references and index.
Keywords: Blood -- Diseases; Graft versus host disease; Hematopoietic stem cells -- Transplantation; Immunology; Hematopoietic Stem Cell Transplantation; Graft vs Host Disease -- immunology; Transplantation Immunology; Transplantation, Homologous -- immunology; Electronic books